On the Use of Chromium Coating for Inner-Side Fuel Cladding Protection: Thickness Identification Based on Fission Fragments Implantation and Damage Profile - Rofida Khamad Khlifa Khamad (2021, 2021)
Inner-side coatings have been proposed as a complementary solution within the accident tolerant fuel (ATF) framework, to provide enhanced protection for the nuclear fuel cladding. Unlike external surface, the degradation of irradiated internal cladding surface has not been studied extensively. Fission fragments produced during the fission of nuclear fuel is one of the key players in this degradation. This study aimed to estimate the minimum thickness of the thin chromium film, required to protect the inner side of the nuclear fuel cladding. The approach used is based on a set of calculations, of Ion ranges and damage profiles, for a group fission fragments, using the TRIM code. The calculation results were verified by comparison with the experimental data associated with the phenomena of the inner cladding degradation of thermo-releasing elements. The recommended minimum thickness for such a film was found to be 9 microns. Calculations also showed that chromium metal has a greater stopping power compared to the zirconium-based alloy E110, which indicates an increased ability of chromium to withstand exposure to energetic fission fragments during reactor operation.